Prognostic implication of CEACAM1 expression in squamous cell carcinoma of the larynx: Pilot study. Issue 6 (23rd December 2018) - Lucarini, Guendalina; Zizzi, Antonio; Re, Massimo; Sayeed, Md. Abu; Di Primio, Roberto; Rubini, Corrado
Abstract: Background: CEACAM1, a valuable biomarker for several cancers, have remained unexplored up to the present in laryngeal squamous cell carcinoma (LSCC). We aimed to examine CEACAM1 expression and evaluate its combinational clinical significance for the diagnosis or prognosis and treatment decision making in LSCC. Methods: CEACAM1 expression was assessed by immunohistochemistry in 54 LSCCs and evaluate its correlation with clinical and histopathological features. Results: CEACAM subtype 1 (CEACAM1) expression was positive in 50% of the cases. No significant difference was observed in relation to age, gender, tumor size, and tumor stage. CEACAM1 expression correlated with tumor grade, development of local recurrence, node and distant metastasis. Kaplan–Meier survival curves showed that CEACAM1 staining was inversely correlated with both overall and disease‐specific 5‐year survival. Conclusions: Our study is the first to demonstrate that CEACAM1 expression is associated with an adverse prognosis in LSCC. CEACAM1 is a valuable biomarker and a promising therapeutic target in LSCC.